Principle-Based Consumption Communities: Exploring the Meanings Derived from Socially Conscious Consumption Practices. (September 2015) - DeVincenzo, Marie Hafey; Scammon, Debra
This exploratory study examines the consumption behavior of people participating in a wind energy program. The authors use the psychological sense of community as a theoretical grounding for the study because it provides a way to examine socially conscious behaviors not solely as the behaviors of individuals but rather as behaviors within a social context with social meaning. The authors analyze indepth interviews using a hermeneutical approach, and the findings identify a principle-based, consumption community to which the informants felt they belonged. The article concludes with a discussion of implications for marketers, policy makers, and environmental activists.